2008
DOI: 10.1590/s1516-35982008000200025
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de sistemas de produção de caprinos leiteiros na Região Sudeste do Brasil

Abstract: confining production systems whereas Capril Pedra Branca bought all the feed while Capril Vale da Braúna produced part of the forage on the farm. In the Capril Via Capri animals were kept on pasture during the day, but received feed supplementation at evening. Technical indexes obtained of those farms were compared and used to identify which components caused more influence on the total costs of the production activity. Herd feeding was the most important item on the productive systems, varying between 60 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 0 publications
0
6
1
16
Order By: Relevance
“…Gonçalves et al (2008) found that herd feeding was the most important item in productive systems, varying between 60 and 70% of the total cost in the southeast of Brazil. In the research area, farmer feeding systems generally depend on grazing, and farmers only use supplemental feed for two or three months especially after births or in hard winter conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Gonçalves et al (2008) found that herd feeding was the most important item in productive systems, varying between 60 and 70% of the total cost in the southeast of Brazil. In the research area, farmer feeding systems generally depend on grazing, and farmers only use supplemental feed for two or three months especially after births or in hard winter conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Esses problemas ocorrem não somente nas regiões brasileiras, mas também em diver sos países que desenvolvem a caprinocul tura leiteira. Dentre os fatores que interferem na realização desta atividade destacam-se: o potencial genético dos rebanhos, a sazonalidade da produção, a qualidade das forrageiras tropicais utilizadas, o clima, manejo, intervalo de partos, a idade ao primeiro parto, o controle das enfermidades, gerenciamen to, nutrição e alimentação dos rebanhos, entre outros (GONÇALVES et al, 2008).…”
Section: Caprinocultura E O Leite De Cabraunclassified
“…In this context, pasture-based animal production is highly dependent on forage production, and particularly in the rainy season, the application of forage surplus conservation methods is required (GONÇALVES et al, 2008). Among forage conservation methods, silage making is widely used by producers due to its simple application.…”
Section: Introductionmentioning
confidence: 99%